FORMULASI JAGUNG MANIS SEBAGAI MEDIA ALTERNATIF PERTUMBUHAN BAKTERI PATOGEN - Yulianto Ade Prasetya (Meditory : The Journal of Medical Laboratory, 2021)
Background: Sources of carbohydrates and proteins to support bacterial growth are available abundance in nature with very affordable prices, including sweet corn. Aims: This research to determine growth of pathogenic bacteria Escherichia coli and Staphylococcus aureus by using sweet corn as an alternative medium with different formulations. Method: The method used was total plate count (TPC) with sweet corn variations used were 1g, 2g, 3g, 4g, and 5g and colony forming units (CFU) were calculated after being incubated for 24 hours at 37C. Result: The result showed that E. coli and S. aureus was able to grow optimally in the variation of 5g with a growth of respectively 46,7 x 107 CFU/mL and 112,7 x 107 CFU/ mL. This research is expected to be used as an alternative medium for routine microbial growth for the purpose of detecting contamination in human biological samples as well as for food and beverage products. Keywords: Sweet corn, Alternative medium, Escherichia coli, Staphylococcus aureus